Tools for forecasting and optimizing the tuning parameter of the lowspeed engine for designing a ship with the kite - Shostak, Vladimir; Kisarova, Alena (Eastern-European Journal of Enterprise Technologies, 2018)
The developed simulation (stochastic) mathematical model for calculating fuel consumption of the main low-speed engine of a transport ship with a kite is proposed. The peculiarity of the model is the use of a number of initial probabilistic quantities such as wave height, wind speed, in the form of inverse integral distribution functions of their values. This makes it possible, using a generator of uniformly distributed pseudo-random numbers, to compute the arrays of possible values of the total fuel consumption of the main engine for the entire future operation and to determine the expected value of consumption. Such a simulation model with a pseudo-random number generator serves as a tool for comparing the fuel consumption of the alternative main engines, differing in the value of the “internal combustion engine – turbocharger” matching parameter. The minimum value of the total fuel consumption corresponds to the optimum value of the matching parameter. Due to the simulation mathematical model, the influence of the “internal combustion engine – turbocharger” matching parameter on the total fuel consumption for the 25-year operation period of the tanker with a deadweight of 26,470 t is investigated with the help of a computer. Its propulsion is provided by the 6S50ME-C7 engine and SkySails 640 m2 kite switched if the winds are favorable. It is found that the optimum matching parameter corresponds to a point on the propeller curve of the engine with a load coordinate of 60.5 % of the rated value. This refers to a round transatlantic voyage in the Northern Atlantic, mainly in temperate latitudes, with prevailing westerlies and northeast trade winds. Fuel economy in the liner shipping at speeds of about 13.5 knots for these conditions due to the use of the kite is 21 %, from the optimization of the mentioned parameter 3.4 % and in general 24.4 %. At the price of fuel for ship diesel engines of USD 322/ton, the expected value of fuel consumption reduction for the medium-range tanker for the specified period is USD 2,029.000 or USD 81,000/year.